The football of the outsiders : Notes about the new ethical conceptions related to the human development of elite athletes - Santome Sánchez, Aldo Alesandro (2019)
This article has carried out a reflection about the phenomenon of football today, analyzing no just like a sport activity, but as a global show and as one of the industries that circulates the most money. In the middle of that context, we did emphasis on the situation of the elite footballers, who, due to the mercantilist vision proposed by several sports institutions, are seen as the